Fork Rib: A Rare Musculoskeletal Etiology of Chest Pain - Rahman, Perdana Aditya; Nasir Aslam, Ahmad Bayhaqi (Universitas Brawijaya, 2020)
Chest pain is a common clinical presentation in daily practice. Musculoskeletal origin is a rare etiology of chest pain, compared to a cardiorespiratory problem and often underrecognized. Fork-rib or bifid-rib is a rare anomaly which uncommonly present with clinical symptoms since in most cases fork-rib incidentally found during cadaveric dissection. Here we report a 27 years old man presenting with chest pain and radiographic examination showing bifid rib of the fifth left rib, without any abnormalities from physical examination and electrocardiography. The patient treated with intravenous painkiller and anticonvulsants. Fork-rib should be considered as a differential diagnosis for chest pain of musculoskeletal origin especially in young adults or chest pain precede with minor trauma.Â